Voltage imbalance analysis in residential low voltage distribution networks with rooftop PVs - Shahnia, Farhad; Majumder, R.; Ghosh, A.; Ledwich, G.; Zare, F. (Elsevier S.A., 2011)
The installation of domestic rooftop photovoltaic cells (PVs) are on the rise due to feed-in tariff and changes driven by environmental concerns. Even though the increase in the PV installation is gradual, their locations and ratings are often random. Therefore, such single-phase bi-directional power flow can have adverse effect on the voltage imbalance of a three-phase distribution network. In this paper, a voltage imbalance sensitivity analysis and stochastic evaluation based on the ratings and locations of single-phase grid-connected rooftop PVs in a residential low voltage distribution network are presented. The stochastic evaluation, based on Monte Carlo method, predicts a failure index of non-standard voltage imbalance in the network in presence of PVs. Some improvement methods are discussed and a new improvement method based on PV converter control is proposed.